강화군 농수산물 유통분야 장기발전계획 수립 연구 - 국승용 (한국농촌경제연구원, 2009)
The world is currently experiencing the accelerated opening of agricultural markets driven by trade agreements and negotiations such as DDA and FTAs and changes in the agricultural policies focused on multi-functions of agriculture. These changes have influence upon domestic agriculture and local administrations as well as rural development plans for the agro-fisheries distribution. Accordingly, the consistent development plans of the agro-fisheries distribution are getting significant in the entire agricultural plans. In this research, the conditions of the ago-fisheries distribution for the chief agricultural products such as Ganghwado rice, Ganghwado turnip, Yellow Sweet Potatoes and Lion-foot wormwood in Ganghwado are examined in depth and the changes of agricultural distribution circumstances are inquired carefully. Based on the result of the research, we think out the strategy of the agro-fisheries distribution revitalization for the Ganghwa products and indicate the optimum agro-fisheries distribution system for Ganghwa products by the reinvigorate of distribution channels such as provision of school lunch and direct business etc. And we carry out a feasibility study of ago-fisheries distribution system for Ganghwa County. In this regard, the following strategies are suggested to realize the vision. First, "Increase regional direct business for Ganghwa ago-fisheries" to build up a stable market. Second, "Conduct the local facilities for providing meals using Ganghwa ago-fisheries" to supply safety products to the local residents. Third, "Set up local ago-fisheries floors" for the local residents to get some places buying and advertising local food. Fourth, "Expand the number of farmer's markets" to increase the income of farmers and fishermen. Fifth, "Raise the value of the rice brand "Ganghwado rice" as good as the Gyeonggi rice brand to promote marketing. Sixth, "Found a local distribution center and export system for Ganghwa agro-fisheries" to improve the present agro-fisheries distribution system and accommodation. Researchers: Seung-yong Gouk, Dong-hoon Kim, Chang-ho Kim E-mail: gouksy@krei.re.kr